Burkina Faso : Second and Third Reviews Under the Extended Credit Facility Arrangement, and Request for Augmentation of Access and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2015)
EXECUTIVE SUMMARY A transition government has been put in place to lead the country to elections in October 2015 and wishes to continue the existing ECF arrangement. The authorities feel the program provides continuity for the transition, and helps safeguard macroeconomic stability, while supporting reforms to address long-standing structural problems. Program performance has been satisfactory, with all performance criteria and most quantitative targets and structural benchmarks met. Staff's assessment is that the transition authorities have the technical capacity and political will to implement the agreed measures. Growth has been revised downwards following multiple shocks. Reductions in commodity prices for the country's two leading exports, the impact of Ebola in the region on tourism and services, and political uncertainty leading up to resignation of Compaore's government in late October 2014 all contributed to a marked slowdown in growth. Real growth is estimated to have been 4 percent in 2014 and is projected at 5 percent for 2015. Lower fiscal revenues forced large spending reduction/import compression. To eliminate large external and fiscal imbalances implied by the shocks and recent depreciation of the CFAF against the US dollar, through the CFAF peg to the euro, the transition government has reduced spending sharply. Even with spending adjustment, revenue measures, and additional budget support commitments from donors, large reserves drawdown will be required meet balance of payment needs. Together with approval of the delayed 2nd review and the 3rd review, the authorities request 40 percent of quota augmentation of access to help meet immediate balance of payments needs. Forward-looking program commitments encompass wide-ranging measures that have both immediate and longer term impacts. Revenue measures aim to reduce fraud and increase revenue intake, along with passage of the long-awaited revised mining code. Spending measures aim to safeguard priority social spending and contain the public wage bill. Extensive reforms are underway to improve budget transparency and cash management, after cash rationing in 2014 gave rise to domestic arrears. Finally, the authorities will implement recommendations of recent audits of state-owned energy companies, including performance contracts to regularize financial obligations and reduce costs, providing scope for better cost recovery, including through more flexible price-setting, in the future.